Seni dan Budaya Tobelo - Galela, Dolfina (Universitas Sam Ratulangi, 2017)
Arts and Culture is everything created humans evolved about how to live together in a group that contains elements of beauty (aesthetics) are down from generation to generation. Not unlike the other regions which have respective areas of art and culture - each. Likewise with Tobelo, which has a strong arts culture, which has a value - the value of cultural hereditary as well as in public life cherish in Tobelo. This study takes the subject of efforts to maintain the existence of cultural arts Tobelo.The purpose of this study is to identify and classify the arts and culture district Tobelo northern Halmahera, North Maluku Province. The results showed that the Cultural Arts Tobelo 'strong as the heritage of art and culture that is passed down from one generation to the next have got education of art and culture since childhood.Keywords: Arts and Culture, TobeloÂ